A Critical Analysis of the Relevance of Educational Linguistic Theory in Al-'Arabiyyah Li Al-Ḥayah: an Arabic Language Textbook - Kania Herliana Kurnia; Tiwi Lestari (Gunung Djati Conference Series, 2026)
Arabic is a very important language, especially in the fields of religion, culture, and education. Therefore, many people wish to learn Arabic properly and correctly. One of the textbooks that is frequently used for learning Arabic is Al-'Arabiyyah li al-Ḥayah. This book has long been used in various schools and language course institutions. This study is important for re-examining Al-'Arabiyyah li al-Ḥayah from educational and linguistic perspectives. The aim is to identify its existing shortcomings and provide recommendations so that the book can be improved and adapted to the needs of contemporary Arabic language learners. This research was conducted using a qualitative method through a library research approach, employing literature review techniques based on books and writings related to the object of the study. The data analysis procedures consisted of data reduction, data presentation, and conclusion drawing. The results of the study on Al-'Arabiyyah li al-Ḥayah indicate that this textbook has demonstrated the implementation of educational linguistic theory principles. On the other hand, the book still possesses several significant shortcomings.